Managing mature forest features: The production, accuracy and ecological relevance of a landscape‐scale map. (31st August 2018) - Koch, Amelia J.; Webb, Matthew; Cawthen, Lisa; Livingston, Daniel; Munks, Sarah A.
Summary: Mature trees and forests contain structural features such as tree hollows, large coarse woody debris and large spreading crowns that provide critical habitat for a wide range of species. These features can take hundreds of years to develop and require careful management to ensure their continued availability. Managing these features requires spatial mapping layers to facilitate landscape‐scale management. This paper outlines how a map of mature forest habitat was developed for Tasmania, Australia. The map was produced using spatial data on vegetation type, mature crown density and senescence, a global layer of forest loss data derived from satellite imagery, a database on timber harvest plans and a spatial layer on the extent of fire. The relationship between mapped mature habitat availability (high, medium, low or negligible) and tree hollow availability in wet forest areas was explored, complementing a similar published study in dry forests. The number of large trees likely to have hollows significantly increased with mapped mature habitat availability, although there was considerable variation and overlap between map categories. Data from a fauna locality database and two radio‐tracking studies showed that three of the vertebrate hollow‐using species examined (Swift Parrot, Common Brushtail Possum and the Tasmanian Long‐eared Bat) and nest records of a species reliant on large tree crowns (the Wedge‐tailed Eagle) were all more likely to occur in areas of higher mapped mature habitat availability. It is concluded that this map reflects the relative availability of tree hollows, is ecologically meaningful and will be useful when managing mature forest habitat at large spatial scales, but the variable accuracy of the map at fine scales needs to be taken into account.